Intelligent Headlight Control by Light Blob Detection - Salam, Amarjit; Kumar, Ashutosh; Idris, Mohammed; Narain, Naman; Sangappa, SB (International Journal of Computer Sciences and Engineering, 2025)
in this paper, we propose an enhanced method for detecting light blobs (LBs) for Intelligent Headlight Control (IHC) using Digital Image Processing Techniques. The main function of the IHC system is to automatically convert high-beam headlights to low beam when vehicles are found in the vicinity. Thus, to implement the IHC, it is necessary to detect preceding or oncoming vehicles. This process of detecting vehicles is done by detecting LBs in the images. Here the algorithm is developed to analyze a frame and the same will be applied to all frames in a video. The area of interest is enhanced by converting the image to binary and thus detecting the LBs. To detect tail lights, red component of the image is extracted. Threshold value can be set depending on the object to be detected. Morphological operations will be performed on the binary image to remove all unwanted objects that are present in the image. Area of the light blob is calculated in the binary image and based on the value of this area, high beam is converted to low beam.